Terapi Akupresur Untuk Mengurangi Rasa Haus Pada Pasien Gagal Jantung dan Gagal Ginjal Kronis : Systematic Review - Kartikaningtyas Kusumastuti; Amelia Amelia; Muhamad Adam; Agung Waluyo (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Thirst is a common complication experienced by patients with heart failure and chronic kidney disease who undergo fluid restriction programs. Without adequate management, thirst can exacerbate the underlying disease due to fluid overload resulting from excessive intake. Acupressure therapy is one of the non-pharmacological interventions that can be implemented by nurses to alleviate thirst. Objective: To explore the effectiveness of acupressure therapy in managing thirst among patients with heart failure and chronic kidney disease. Methods: This study employed a systematic review method based on the PRISMA guidelines. Articles were retrieved from databases including Pubmed, ScienceDirect, ProQuest, Sage Journals, and Taylor and Franchis, as well as other sources published before 2025. Article selection was conducted according to inclusion and exclusion criteria, followed by critical analysis using the JBI Crit ical Appraisal Checklist. Results: Out of 4,628 articles, 6 RCTs and 1 quasi-experimental study were included in the analysis. The results indicated that acupressure, both body and auricular acupressure, was effective in reducing thirst intensity, thirst distress, and xerostomia in patients with heart failure and chronic kidney disease. Conclusion: Acupressure therapy can serve as an alternative nursing intervention to alleviate thirst in patients with heart failure and chronic kidney disease.